2007
DOI: 10.1017/s1751731107710303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary crude protein level on odour from pig manure

Abstract: The objective of this study was to determine the effects of dietary crude protein (CP) level on odour emission, odour intensity, hedonic tone, and ammonia emission from pig manure and on manure composition (pH, total nitrogen, ammonium, volatile fatty acids, indolic, phenolic and sulphur-containing compounds). An experiment was conducted with growing pigs (n ¼ 18) in a randomised complete-block design with three treatments in six blocks. Treatment groups were 12%, 15% and 18% CP diets. Barley was exchanged for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
29
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 27 publications
(31 reference statements)
11
29
0
5
Order By: Relevance
“…The net height of the lower compartment (storage container) was 41.5 cm and the net height of the upper compartment was 41.5 cm. A schematic view of the odour sample collection system, which was adapted from Le et al (2007), is illustrated in Figure 1.…”
Section: Experimental Dietsmentioning
confidence: 99%
“…The net height of the lower compartment (storage container) was 41.5 cm and the net height of the upper compartment was 41.5 cm. A schematic view of the odour sample collection system, which was adapted from Le et al (2007), is illustrated in Figure 1.…”
Section: Experimental Dietsmentioning
confidence: 99%
“…Le et al (22) mostraron que alimentar a los cerdos con dietas con 18 y 12 % PC disminuía el pH de las excretas de 7.83 a 7.10. En contraste, otros autores (23) no pudieron detectar diferencias en el pH del purín cuando alimentaron a cerdos en crecimiento con dietas cuyo contenido de PC fue del 19 o del 22 %; esta falta de efecto, pudiera estar asociada al hecho de que el rango en los niveles de PC que usaron fue más elevado y estrecho que en otros estudios, incluyendo éste.…”
Section: Discussionunclassified
“…It has been widely demonstrated that FC incorporated into pig diets increases the volatile fatty acid (VFA) content in manure (Clark et al, 2005;Kerr et al, 2006;O'Connell et al, 2006), but it remains unclear whether the odour profile is affected. Whereas Lynch et al (2008) obtained a 41% increase of odour emissions when sugar beet pulp was added to pig diets, a non-significant effect of FC was found by Clark et al (2005) and Le et al (2007). As acknowledged by Leek et al (2007) and Le et al (2008), the balance between dietary FC and CP plays an important role on odour production and emission.…”
Section: Dietary Manipulationmentioning
confidence: 91%
“…It has been demonstrated that reducing crude protein (CP) can effectively reduce the proportion of excreted nitrogen, which is associated to lower ammonia emissions, not only at the housing level, but also during manure storage and land application of manure (Hayes et al, 2004;Le et al, 2007). However, the cause and effect relationship between feed characteristics and the excretion of odorous compounds is not so evident.…”
Section: Dietary Manipulationmentioning
confidence: 99%
See 1 more Smart Citation